European Union crises and Irish public opinion: continuity and change in patterns of support. Issue 4 (2nd October 2019) - Simpson, Kathryn
ABSTRACT: Individuals in Ireland are among the most enthusiastic supporters of European integration since European Union (EU) accession in 1973, and are often labelled 'good Europeans with a pro-integrationist attitude'. The 2008 financial crisis is regarded as a turning point in Ireland's relationship with the EU as a result of the economic downturn and the widening of economic disparities experienced by individuals. Meanwhile, Brexit poses significant and specific challenges to Ireland and has the capacity to impact Irish attitudes towards the EU. Using a combination of Standard Eurobarometer data from 2007 to 2018 and a variety of opinion polling data, this paper examines how the economic crisis and Brexit have shaped Irish attitudes towards the EU.